First and second Thessalonians - Brookins, Timothy (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2021)
"A practical commentary on First and Second Thessalonians that is conversant with contemporary scholarship, draws on ancient backgrounds, and attends to the theological nature of the texts"--
Includes bibliographical references and index
Keywords: Bible -- Commentaries; Kommentar